A theoretical model for understanding relationship functioning in intercultural romantic couples. Issue 4 (9th November 2020) - Fonseca, Ana Laura; Ye, Tony; Koyama, Jill; Curran, Melissa; Butler, Emily A.
Abstract: Intercultural romantic relationships have increased worldwide. Yet, there is a lack of empirical knowledge about intercultural couples. The studies that do suggest that intercultural couples have higher rates of conflict and long‐term instability, but most studies have measured intercultural couples using categorical responses of race/ethnicity, which limits theoretical insight to the interpersonal characteristics that make up high‐quality intimate relationships. This review integrates findings from several research fields into a new model, called the culturally based romantic relationship (CBR 2 ) model, to understand how similarities/differences in within‐person emotional processes and relationship norms relate to between‐person emotional functioning, and in turn relationship quality. Theoretical models of this nature are essential because they can impact therapy and counseling programs developed for diverse groups of people, but also advance research fields that are related to culture, emotions, and interpersonal relationships.